Knowledge, attitude and practice toward birth preparedness and complication readiness among antenatal women: a cross-sectional study at a tertiary hospital - S., Loshini; S., Ganga; Gnanasekaran, Vijayalakshmi; Ganitha, G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Birth preparedness and complication readiness (BP/CR) is a key strategy to reduce maternal morbidity and mortality by minimizing delays in recognizing complications and accessing timely care. Despite improvements in antenatal care utilization, gaps in awareness of obstetric danger signs persist. The objective of the study was to assess the knowledge, attitude, and practice of BP/CR among antenatal women attending a tertiary healthcare facility. Methods: A hospital-based cross-sectional study was conducted among 467 antenatal women (≥24 weeks gestation) at a tertiary care centre in Chennai between January and June 2025. Participants were enrolled using convenience sampling. Data were collected using a structured questionnaire assessing knowledge, attitude, and practice domains. Statistical analysis was performed using Stata v16, with associations tested using chi-square and t-tests. Results: Only 36.8% of women demonstrated adequate knowledge of danger signs, whereas 64.9% had good knowledge of BP/CR components. A positive attitude toward BP/CR was observed in 70.2%, and 59.7% reported adequate preparedness. Adequate knowledge and practice were significantly associated with higher maternal education, employment, husband’s literacy, and higher socioeconomic status (p<0.05). Multiparity was associated with better knowledge, while later gestational age correlated with a more positive attitude. Conclusions: Although attitudes and preparedness toward BP/CR were relatively favorable, awareness of danger signs remains inadequate. Strengthening antenatal counselling with emphasis on early recognition of complications, along with addressing socioeconomic disparities and promoting partner involvement, is essential to improve maternal health outcomes.